Z dziejów kultu św. Antoniego z Padwy w Bydgoszczy przedrozbiorowej (Kronika Bydgoska, 2013)
The cult of Saint Anthony of Padua was initiated in Bydgoszcz by the local Bernardine monastery in the middle of the 17th century. An altar was made and a fraternity of this saint was established in the monasterial church. The cult quickly developed thanks to numerous grants and gifts, mainly from the Raczyński family. The altar was their burial place. Through the intercession of the saint, there were miracles connected with restorations to health and finding lost things. The saint’s miraculous power was famous not only in Kuyavia. To a lesser extent the saint was worshipped at the parish church, the convent of the nuns of St Clare, featuring modest altars of the saint and few votive offerings.